2020
DOI: 10.1177/1403494820956452
|View full text |Cite
|
Sign up to set email alerts
|

The New Patterns study: coordinated measures to combat child poverty

Abstract: Background Child poverty rates are rising in Norway with potential negative consequences for children. Services for families with low income are often fragmented and poorly integrated, and few coordinated initiatives have been implemented and evaluated in Norway. Aims: The aim of the current study is to evaluate how integrated and coordinated services provided over a prolonged period by a family coordinator are related to changes across a wide range of health, wellbeing and home environment indicators for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Importantly, previous studies have found lower SDQ scores among Nordic children and adolescents compared with peers in other (European) countries,29 so the scores obtained in the current study are higher than what has been reported previously. The finding of more symptoms of mental health problems in this sample can probably be attributed to the risk associated with low income and the challenging living conditions that characterises this sample 14…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Importantly, previous studies have found lower SDQ scores among Nordic children and adolescents compared with peers in other (European) countries,29 so the scores obtained in the current study are higher than what has been reported previously. The finding of more symptoms of mental health problems in this sample can probably be attributed to the risk associated with low income and the challenging living conditions that characterises this sample 14…”
Section: Discussionmentioning
confidence: 76%
“…The finding of more symptoms of mental health problems in this sample can probably be attributed to the risk associated with low income and the challenging living conditions that characterises this sample. 14 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the feasibility phase, the social-prescribing intervention will be tested in urban and rural areas of Denmark, whereas the participating cases from general practices and SCs will have different delivery contexts. Hence, the test and refinement of the programme theory are based on diverse feasibility studies, and the results of the ‘Move More’ study are thus expected to be relevant beyond the participating cases [30]. Furthermore, we consider the perspectives and resources of key stakeholders when developing the intervention, which is expected to maximise acceptability and ensure favourable conditions for planning future implementation.…”
Section: Discussionmentioning
confidence: 99%